Transnational postgraduates: navigating academic trajectories in the globalized university. Issue 3 (3rd July 2021) - Hou, Minghui; Cruz, Natalie; Glass, Chris R.; Lee, Sherrie
ABSTRACT: This article explores the academic trajectories of transnational postgraduates. We draw upon interrelated theories of globalization and transnational social fields to frame the globalizing social and educational contexts in which international students navigate their lives and careers after earning doctoral degrees. We draw on in-depth interviews where transnational postgraduates' voices are placed at the center of the findings, and we explore how their background, journey, and environment simultaneously shaped them as well as transformed the spaces they inhabited. We highlight how the movement of transnational postgraduates is not simply a transfer from one physical location to another, but rather that the movement itself constitutes and structures a new space of identification and of belonging and global imagination.